Alltagskommunikation und Lexikographie - Dobrovolskij, Dmitrii (Wydawcnictwo Naukowe UAM, 1994)
The paper presents an analysis of some important aspects of everyday communication and their reflection in modern learner’s dictionaries. The basic unit of lexicographic description is a situational utterance, i.e. a linguistic entity which can be considered as a unit only from a functional (not a taxonomic) point of view. Lexicographic presentation of situational utterances has to include not only linguistic data but also information about relevant conceptual structures: frames and scripts. This attempt to present communicative situations with all their relevant components in learner’s dictionaries is exemplified by a new German-Russian dictionary which the authors are working on.